2020
DOI: 10.1103/physrevb.101.064406
|View full text |Cite
|
Sign up to set email alerts
|

Revealing quantum chaos with machine learning

Abstract: Understanding the properties of quantum matter is an outstanding challenge in science. In this work, we demonstrate how machine learning methods can be successfully applied for the classification of various regimes in single-particle and many-body systems. We realize neural network algorithms that perform a classification between regular and chaotic behavior in quantum billiard models with remarkably high accuracy. By taking this method further, we show that machine learning techniques allow to pin down the tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 64 publications
0
31
0
Order By: Relevance
“…AD today has numerous applications across a variety of domains. Examples include intrusion detection in cybersecurity [15]- [20], fraud detection in finance, insurance, healthcare, and telecommunication [21]- [27], industrial fault and damage detection [28]- [36], the monitoring of infrastructure [37], [38] and stock markets [39], [40], acoustic novelty detection [41]- [45], medical diagnosis [46]- [60] and disease outbreak detection [61], [62], event detection in the earth sciences [63]- [68], and scientific discovery in chemistry [69], [70], bioinformatics [71], genetics [72], [73], physics [74], [75], and astronomy [76]- [79]. The data available in these domains is continually growing in size.…”
Section: Introductionmentioning
confidence: 99%
“…AD today has numerous applications across a variety of domains. Examples include intrusion detection in cybersecurity [15]- [20], fraud detection in finance, insurance, healthcare, and telecommunication [21]- [27], industrial fault and damage detection [28]- [36], the monitoring of infrastructure [37], [38] and stock markets [39], [40], acoustic novelty detection [41]- [45], medical diagnosis [46]- [60] and disease outbreak detection [61], [62], event detection in the earth sciences [63]- [68], and scientific discovery in chemistry [69], [70], bioinformatics [71], genetics [72], [73], physics [74], [75], and astronomy [76]- [79]. The data available in these domains is continually growing in size.…”
Section: Introductionmentioning
confidence: 99%
“…Artificial neural networks (NNs), one of the most efficient and widely used tools of ML [8], are currently at the frontier of research activity. It has been shown that they are capable of predicting phase transitions and critical temperatures [9][10][11][12][13][14][15][16][17][18][19], learning topological indices of quantum phases [20][21][22][23][24][25][26], efficiently representing many-body states [27][28][29][30][31][32][33][34], improving known numerical computational methods [35][36][37], and decoding topological quantum correcting codes [38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…transition) sampling problem. In addition, study of quantum many body systems using Machine Learning is applied to simulation of the quantum spin dynamics 26 , 27 , identifying phase transitions 28 , and solves the exponential complexity of the many body problem in quantum systems 29 .…”
Section: Introductionmentioning
confidence: 99%
“…www.nature.com/scientificreports/ is applied to simulation of the quantum spin dynamics 26,27 , identifying phase transitions 28 , and solves the exponential complexity of the many body problem in quantum systems 29 .…”
mentioning
confidence: 99%